The Relevance of Thomas Lickona's Character Education Concept and its Implication for Islamic Education in Schools - Yandi Hafizallah (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
School is a vehicle for every child of the nation as a process of character building, not enough with the many subjects given but through extracurricular activities is also very influential in helping the formation of good character. The purpose of this research seeks to discuss the concept of character education from the perspective of Thomas Lickona and its implications for Islamic Education in Schools. This research uses a library research approach. The collection uses documentation studies. Data analysis uses four steps, namely (1) Data collection; (2) Data reduction; (3) Data display; (4) Conclusion/verification. The conclusion of the research found that Thomas Lickona's concept of character education regarding moral knowledge, moral feelings, and moral actions is very relevant to the Islamic world, where the world of Islamic education highly emphasizes three values, namely morals, manners, and exemplary, all of which demand to be applied in social life. The contribution of this research is as a reference for insight and knowledge for formal educational institutions or teachers who want to foster or shape character through Islamic religious education subjects.